2009
DOI: 10.1111/j.1365-2958.2009.06766.x
|View full text |Cite
|
Sign up to set email alerts
|

The essential histone‐like protein HU plays a major role in Deinococcus radiodurans nucleoid compaction

Abstract: The nucleoid of radioresistant bacteria, including D. radiodurans, adopts a highly condensed structure that remains unaltered after exposure to high doses of irradiation. This structure may contribute to radioresistance by preventing the dispersion of DNA fragments generated by irradiation. In this report, we focused our study on the role of HU protein, a nucleoid-associated protein referred to as a histone-like protein, in the nucleoid compaction of D. radiodurans. We demonstrate, using a new system allowing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(81 citation statements)
references
References 53 publications
3
78
0
Order By: Relevance
“…For example, deletion of HU from the E. coli genome is not lethal unless IHF and H-NS are deleted as well (31). In contrast, the disruption of HU is lethal for organisms in which it is the only NAP available (23,32,33). For H. pylori, we can easily obtain hup mutant strains which show normal growth at the exponential growth phase in vitro (15).…”
Section: Discussionmentioning
confidence: 99%
“…For example, deletion of HU from the E. coli genome is not lethal unless IHF and H-NS are deleted as well (31). In contrast, the disruption of HU is lethal for organisms in which it is the only NAP available (23,32,33). For H. pylori, we can easily obtain hup mutant strains which show normal growth at the exponential growth phase in vitro (15).…”
Section: Discussionmentioning
confidence: 99%
“…HU binds to four-way DNA junctions and may be additionally optimized for DNA recombination events by stabilizing recombination intermediates (208,209). Contrary to HU, one of the D. radiodurans Dps ("DNA protection during starvation") proteins, Dps1 (DR2263), was shown to promote DNA compaction in vitro (54) but not in vivo, as its depletion has no effect on genome condensation and cell viability (459). The D. radiodurans SMC ("structural maintenance of chromosomes") protein (DR1471), which is important for genome stabilization and DNA repair in eukaryotes (100, 365) and bacteria (640), has no role in genome condensation in D. radiodurans either (140a).…”
Section: Recombinational Processes In D Radiodurans Dna Repairmentioning
confidence: 99%
“…In vivo studies showed that the D. radiodurans HU ortholog (DRA0065) plays a major role in nucleoid organization and DNA compaction in D. radiodurans (459). It is essential for cell viability, as its progressive depletion leads to the decondensation of DNA, the fractionation of the nucleoid, and cell lysis (459).…”
Section: Recombinational Processes In D Radiodurans Dna Repairmentioning
confidence: 99%
See 2 more Smart Citations